http://www.sportmont.ucg.ac.me/clanci/SportMont_Maj_2007_Mijajlovic_725-731.pdf - Miodrag Drapšin; Patrik Drid (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
This work represents the motor testing results within the two groups of wrestlers and boxers who are current members of national team. The results of mentioned testing show the existence of signifi cant differences in the motor space and therefore emphasize the statistical meaning. The wrestlers' group attains values of the measured variables very close to the results that are published by the other authors, meanwhile the boxers group fails behind world's standards.